State of India’s Digital Economy in 2026: A Review - Das, Anup Kumar (Journal of Data Science, Informetrics, and Citation Studies, 2026)
The "State of India's Digital Economy (SIDE) 2026" report, published by the ICRIER-Prosus Centre for Internet and Digital Economy (IPCIDE) and authored by Deepak Mishra, Aarti Reddy, Shailly Gupta, and Agrima Khanduri, is a highly comprehensive benchmarking study. Expanded in its 5th edition to cover 71 countries representing 96% of global GDP, 86% of global internet users, and 83% of the global population, the report offers a rigorous assessment of the global digital landscape with a particular focus on India's position within it (p. 13). The Report is divided into six chapters, namely, The Global Digital Map: Who Leads and Who Lags in 2026; The Rise of the Intelligent Digital Economy; Digitalisation’s Hidden Costs: Global Imbalance, Digital Crime, and E-Waste; India in the G20: An Emerging Digital Power with Significant Room to Grow; India and BRICS: Competing with Emerging Giants, and India and the EU: A Partnership of Complementary Strengths.
Keywords: Digital Economy; Book Review